2017
DOI: 10.3390/rs9101078
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Soil Spectral Response and Properties Assessment: Effects of Measurement Protocol and Data Mining Technique

Abstract: Abstract:Soil spectroscopy has shown to be a fast, cost-effective, environmentally friendly, non-destructive, reproducible and repeatable analytical technique. Soil components, as well as types of instruments, protocols, sampling methods, sample preparation, spectral acquisition techniques and analytical algorithms have a combined influence on the final performance. Therefore, it is important to characterize these differences and to introduce an effective approach in order to minimize the technical factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 48 publications
1
33
0
1
Order By: Relevance
“…Currently, visible and nearinfrared (VIS-NIR) spectroscopy represents an alternative method for soil analysis and quantification. The method is faster, non-destructive, environmentally friendly, has a repeatable analytical technique and requires minimal sample preparation (Gholizadeh et al 2017). Its implementation in the field and laboratory offers the possibility of repeating measurements and estimating the ranges of various soil properties such as OM content, texture and CaCO 3 (Lagacherie et al 2008, Liu et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, visible and nearinfrared (VIS-NIR) spectroscopy represents an alternative method for soil analysis and quantification. The method is faster, non-destructive, environmentally friendly, has a repeatable analytical technique and requires minimal sample preparation (Gholizadeh et al 2017). Its implementation in the field and laboratory offers the possibility of repeating measurements and estimating the ranges of various soil properties such as OM content, texture and CaCO 3 (Lagacherie et al 2008, Liu et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Gholizadeh et al [11] also stated that one way of minimizing the undesirable impacts is by adopting advanced preprocessing methods as well as the appropriate selection of multivariate statistical analysis algorithms. These approaches can significantly decrease the differences between spectral measurements of samples assessed by different operators and systems under different conditions [12] and improve the obtained prediction accuracy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors that can influence the spectroscopy for soil properties determination are spectral resolution, which was shown not to have a significant effect on predictions (Knadel et al, 2013;Rossel et al, 2016). Another study indicated that scanning protocols may not have a significant impact on prediction if the standard is considered with enough care (Gholizadeh, Carmon, Klement, Ben-Dor, & Borůvka, 2017). However, some studies have shown that different calibration models, such as the most widely used models of Cubist regression tree, partial least squares regression (PLSR) and support vector machine (SVM), can produce different prediction accuracies for soil properties (Minasny & McBratney, 2008;Morellos et al, 2016;Rossel & Behrens, 2010).…”
mentioning
confidence: 99%